PATHOLOGIC COGNITIVE FACTORS OF BOYS FROM HIGH SCHOOL AFTER WAR PERIOD - Midhat Mekić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Aim of this research was to define latent structural sistem of pathological cognitive characteristics of boys from high school JU M.S.S., Gračanica. Using tests 18 PF, in the aim of research we made measuring of pathological cognitive characteristics on group of 127 pupils who were 18 and 19 years old. Analyzing cognitive characteristics we had got three types of factors. Characteristics of of person we had characterized with konverzivnim, steničnim i asteničnim syndromes and all important coeficients were with postive sign. Result we had got could be used by experts for high school plan and program making